Analisis Kelelahan Kerja Subjektif dengan Menggunakan Kuesioner Subjective Self Rating Test - Fajrin Septia Putrisani; Asep Erik Nugraha; Dene Herwanto (Universitas Indraprasta PGRI Jakarta, 2023)
Occupational health and safety need to be carried out properly in a job as an effort to reduce the occurrence of work fatigue. Work fatigue is a condition in which a person experiences both physical and mental deterioration. When someone experiences work fatigue, his work productivity, efficiency and effectiveness can also decrease. Excessive working time from existing rules can result in work fatigue. PT. United Steel Center has a division with a very long working time duration of 33,420 minutes or 557 hours in February 2022. Based on this, it is necessary to conduct an analysis to find out whether there is subjective fatigue in machine operators in the division. This study uses the method of Subjective Self Rating Test (SSRT). Based on the results of distributing the SSRT questionnaire and analysis, it is known that from eight operators, there are seven operators who experience low work fatigue, while one operator experiences high work fatigue.